Kualitas Kimia dan Organoleptik Yoghurt yang dibuat Menggunakan Kultur Yoghurt dan Jenis Susu yang Berbeda - Astri Mersiana Timo; Theresia Ika Purwantiningsih (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
This study aims to determine the chemical and organoleptic quality of yoghurt made using different milk and yoghurt culture types. This research was carried out on January 2020. Located at the Faculty of Agriculture Laboratory of the University of Timor Kefamenanu (for organoleptic testing of yoghurt) and at the Faculty of Chemistry Laboratory Nusa Cendana Kupang Animal Husbandry (for testing pH, lactic acid levels, protein content and fat content). In this study using the 3 type of (fresh milk, UHT milk (Ultra High Temperature) and powdered milk), the experimental design used was a Completely Randomized Design (CRD) with 3treatments 3 replications so that there were 9 sample trial units. The treatment consisted of R0= Fresh milk, R1= UHT milk and R2= Milk powder. Based on the results of statistical analysis that the use of different types of milk showed significant or significant differences (P˂ 0,05). The use of fresh milk can give a good color of yoghurt that is equal to 1,77 which shows the yoghurt is yellowish white. The aroma of the best yoghurt is found in the UHT milk type which is 2,74 which shows the yoghurt is flavorful. The best yughurt texture is found in the type UHT milk that yoghurt is rather thick texture. The best acidity level of yoghurt is found in the UHT milk type which is 3,04 which shows that the yoghurt has acidic level, the good level of yoghurt preference is found in the type of milk powder of 2,37 which indicates that the yoghurt has a level of liking like. The best pH yoghurt in fresh milk is 4,35. The best level of lactic acid in milk powder is 0,78%. The best protein content in fresh milk is 2,86% and the best yoghurt fat content in the type of milk powder 0,30%. The conclusion of this study is the type of UHT milk is a type of milk that is better used in making yoghurt. When compared with the type of fresh milk and milk powder in terms of aroma, texture, acidity, Ph and protein content.